2017
DOI: 10.1108/jarhe-05-2016-0039
|View full text |Cite
|
Sign up to set email alerts
|

Generation “X” and “Y” knowledge sharing behaviour

Abstract: Purpose The purpose of this paper is to investigate the relationship between employee motivation and intention for knowledge sharing behaviour. Inter-generational differences (generations X and Y only) were assumed to moderate in the relationship between intention and knowledge sharing behaviour of non-academic staff of higher learning institutions. This research also aims to test the role of behavioural intention as mediation between motivation and knowledge sharing behaviour. Design/methodology/approach Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Several studies have found that each generation has different attitudes about KSB. In the current era, organizations are dominated by the "X" generation (born in the late 1960s and early 1980s) and the "Y" generation (born in the early 1980s to early 2000s) (Rahman et al, 2017). Generation "X" is said to focus more on work because it is motivated to continue earning money, whereas generation "Y" focuses more on finding the meaning of life (Asghar, 2014).…”
Section: Generational Differencesmentioning
confidence: 99%
“…Several studies have found that each generation has different attitudes about KSB. In the current era, organizations are dominated by the "X" generation (born in the late 1960s and early 1980s) and the "Y" generation (born in the early 1980s to early 2000s) (Rahman et al, 2017). Generation "X" is said to focus more on work because it is motivated to continue earning money, whereas generation "Y" focuses more on finding the meaning of life (Asghar, 2014).…”
Section: Generational Differencesmentioning
confidence: 99%
“…Gen Y employees seek challenging and satisfying job roles to develop their professional competencies (Twenge, 2010). Whilst, Gen “X” is said to be more focused on money making, Gen “Y” is more global and is focused on making their life meaningful (Rahman et al ., 2017). Also, the study results supported that meaningfulness in work mediated the relationship between job crafting and intention to stay ( β = 0.37, p < 0.05), thus providing partial support to H7.…”
Section: Discussionmentioning
confidence: 99%
“…Land area affects the application of innovation (Gandasari et al, 2021). Generation will determine individuals in knowledge-sharing activities (Rahman et al, 2017;Obermayer and Toth, 2020;Kaba et al, 2023). A person's actors in the supply chain will shape communication behavior and knowledgesharing to fulfill their role (Ellyta et al, 2019;Halim et al, 2019).…”
Section: Case Study Design and Research Informantsmentioning
confidence: 99%